A Comprehensive Framework for Enhancing Blockchain Security and Privacy - Faisal Yusuf; Riya Widayanti; Sausan Raihana Putri; Aulia Wellington (Blockchain Frontier Technology, 2025)
Blockchain technology has gained widespread adoption across various industries due to its decentralized and transparent nature. However, its inherent characteristics, such as immutability and openness, expose the system to critical security threats and privacy concerns. This study aims to develop a comprehensive framework to enhance blockchain security and privacy, addressing prevalent challenges such as data breaches, transaction anonymity, and resistance to cyberattacks. The proposed framework integrates advanced cryptographic techniques, including Zero Knowledge Proofs (ZKP), Secure Multi Party Computation (SMPC), and enhanced encryption protocols, alongside innovative consensus mechanisms to improve system robustness. A simulation-based evaluation and a real-world case study were conducted to validate the framework. The results demonstrate significant improvements in mitigating security vulnerabilities, such as 51% attacks and double spending, while ensuring enhanced privacy through anonymized data handling and confidentiality-preserving transactions. Furthermore, the case study confirmed the framework's practicality and adaptability across diverse applications. These findings highlight the proposed framework's potential to establish a secure and privacy-preserving blockchain ecosystem, offering a solid foundation for future research and implementation in both public and private blockchain networks.